A Crystal-Chemical Framework for Relaxor versus Normal Ferroelectric Behavior in Tetragonal Tungsten Bronzes - Zhu, X.
Tetragonal tungsten bronzes (TTBs), an important class of oxides known to exhibit ferroelectricity, undergo complex distortions, including rotations of,oxygen octahedra, which give rise to either incommensurately or commensurately modulated superstructures. Many TTBs display broad, frequency-dependent relaxor dieletric behavior rather than sharper frequency-independent normal ferroelectric anomalies, but the exact reasons that favor a particular type of dielectric response for a given composition remain unclear. In this contribution the influence of incommensurate/commensurate dispiacive modulations on the onset of relaxor/ferroelectric behavior in TTBs is assessed in the context of basic crystal-chemical factors, such as positional disorder, ionic radii and polarizabilities, and point defects. We present a predictive crystal-chemical model that rationalizes composition structure properties relations for a broad range of TTB systems.